Finding Common Ground in Collaborative Environmental Management: A Case Study in Cijedil Forest Landscape, Cianjur - Agung Hasan Lukman; Budhi Gunawan; Parikesit Parikesit (Jurnal Ilmu Lingkungan, 2021)
Forest landscape in Cijedil Village, Cianjur hosts numerous endemic wildlife to conserve. On the other hand, the needs of local people from forest utilization could not be also neglected. Hence, the environmental management issues in the forest landscape of Cijedil are not only attributed to the biodiversity and ecological protection but also social and economic empowerment that engages various stakeholders. To get a mutual understanding among the stakeholders within collaborative management, building dialogue, reaching consensus, and comprehending its process is necessary. Nevertheless, few studies, particularly in Indonesia, have thoroughly performed related to this topic. The objective of this study is to fill this gap by describing the consensus building in the collaborative process framework and its affecting factors for reaching an agreement in collaborative management in the forest landscape of Cijedil. We performed a qualitative study by using action-based research and a case-study approach. Semi-structured and in-depth interviews were undertaken with 18 key informants selected by the snowball sampling representing six stakeholders involved: KPH Cianjur, SPH II Cianjur, BLHD Cianjur, officials of Cijedil Village, LMDH Cijedil, and the local community of Cijedil. The findings show that this consensus building has adapted the collaborative framework indicated by problem- and direction-setting activities in the first two stages of the collaborative process. It also suggests that the main influencing of parties-related factors are human resource capacity, level of understanding, and commitment, whereas process-related barriers are time uncertainty and incentives offered. These factors are indicated not completely discrete but rather affecting each other. To conclude, while the consensus for broadly collaborative environmental management is still needed to promote, the driven inhibiting factors remain. It is, therefore, crucial to address and deal with those main challenging elements. AbstrakLanskap hutan di Desa Cijedil, Cianjur mempunyai banyak satwa endemik yang penting untuk dilestarikan. Namun di sisi lain, kebutuhan masyarakat lokal dari pemanfaatan hutan juga tidak bisa diabaikan. Oleh karena itu, masalah pengelolaan lingkungan di lanskap hutan Cijedil tidak hanya terkait dengan perlindungan keanekaragaman hayati tetapi juga pemberdayaan sosial dan ekonomi yang melibatkan berbagai pemangku kepentingan. Untuk mendapatkan pemahaman bersama di antara para pemangku kepentingan dalam pengelolaan kolaboratif, perlu membangun dialog, mencapai konsensus, dan memahami prosesnya. Namun demikian, baru sedikit penelitian, khususnya di Indonesia, yang telah dilakukan terkait topik ini. Tujuan dari studi ini adalah untuk mengisi kesenjangan ini dengan menggambarkan pembangunan konsensus dalam kerangka proses kolaboratif dan faktor-faktor yang mempengaruhinya untuk mencapai konsensus dalam pengelolaan kolaboratif di lanskap hutan Cijedil. Penelitian ini merupakan penelitian kualitatif berbasis aksi dan pendekatan studi kasus. Wawancara semi terstruktur dan mendalam dilakukan dengan teknik snowball terhadap informan kunci yang mewakili enam pemangku kepentingan yang terlibat: KPH Cianjur, SPH II Cianjur, BLHD Cianjur, aparat Desa Cijedil, LMDH Cijedil, dan masyarakat Cijedil. Temuan menunjukkan bahwa pembangunan konsensus ini telah mengadaptasi kerangka kerja kolaboratif yang ditunjukkan oleh aktivitas penetapan masalah dan arah dalam dua tahap pertama proses kolaboratif. Temuan juga menunjukkan bahwa faktor utama yang mempengaruhi terkait pihak adalah kapasitas sumber daya manusia, tingkat pemahaman, dan komitmen, sedangkan hambatan terkait proses adalah ketidakpastian waktu dan insentif yang ditawarkan. Faktor-faktor ini tidak sepenuhnya terpisah melainkan saling mempengaruhi. Penelitian ini menyimpulkan bahwa walaupun konsensus untuk pengelolaan lingkungan kolaboratif secara luas masih diperlukan, faktor-faktor penghambatnya masih tetap ada. Oleh karena itu, penting untuk mengatasi tantangan utama tersebut.